Measuring the performance of the virtual teams in global software development projects - Gheni A.Y.; Jusoh Y.Y.; Jabbar M.A.; Ali N.M.; Shanmugam M.; Yousif H.A. (University of Tehran, 2023)
The development teams who are geographically spread, culturally mixed and mainly depend on information and communication technology (ICT) for communication is defined as a global virtual teams (GVTs). Despite the advancement of technologies, achieving the efficient performance of GVTs remains a challenge. The reviewed literature has highlighted the importance of training and development, organizational commitment and motivation in enhancing the performance of GVTs. This study aims to identify the key performance indicators (KPIs), measures, and variables for assisting the GVT performance in global software development projects (GSD). In addition, this study aims to measure the GVTs performance involving online training and development, organizational commitment, and motivation in GSD projects. A survey was conducted among 103 respondents. Then, the performance measurement model (PMM) for GVTs in GSD projects was proposed based on the result of the survey. Finally, the project managers validated the study model. The proposed PMM includes four major components, namely performance measurement processes, mapping strategy for performance evaluation, measurements and performance analysis. The results showed the validity of the proposed model and confirmed that the PMM can assist project managers in measuring the performance of GVTs in GSD Projects. University of Tehran, Faculty of Management